Epistemologic basis of the post degree training process in statistics for graduates in Health Information Systems - Bolívar Alejandro Pérez Rodríguez; Isabel Alonso Berenguer; Eduardo López Hung; Antonio Salgado Castillo; José Antúnez Coca (Centro Provincial de Información de Ciencias Médicas, 2019)
The Health National System acquires a higher development every day and has a technological equipment according to the science and technique progress, so it requires a professional training that responds to its interests and demands. To such effects,  the process of post degree training in statistics for the graduates in  Health Information Systems is epistemologically supported in this work, taking into account its significance as a training-investigative process, as well as the professional training as one of the post degree subsystems, guided to the solution of problems related to the updating and systematizing of knowledge, which will allow  graduates to reach a performance level according to the scientific, technological, social, economic and cultural development, manifested in their professional practice.